Alpha‐kinase 1 (ALPK1) agonist DF‐006 demonstrates potent efficacy in mouse and primary human hepatocyte (PHH) models of hepatitis B. Issue 1 (17th January 2023) - Xu, Cong; Fan, Jieqing; Liu, Danyang; Tuerdi, Aimaier; Chen, Juanjuan; Wei, Yuning; Pan, Yanfang; Dang, Huaixin; Wei, Xiong; Yousif, Ashraf Siddig; Yogaratnam, Jeysen; Zhou, Qiong; et al.
Abstract : Background and Aims: In the treatment of chronic hepatitis B (CHB) infection, stimulation of innate immunity may lead to hepatitis B virus (HBV) cure. Alpha‐kinase 1 (ALPK1) is a pattern recognition receptor (PRR) that activates the NF‐κB pathway and stimulates innate immunity. Here we characterized the preclinical anti‐HBV efficacy of DF‐006, an orally active agonist of ALPK1 currently in clinical development for CHB. Approach and Results: In adeno‐associated virus (AAV)‐HBV mouse models and primary human hepatocytes (PHHs) infected with HBV, we evaluated the antiviral efficacy of DF‐006. In the mouse models, DF‐006 rapidly reduced serum HBV DNA, hepatitis B surface antigen, and hepatitis B e antigen levels using doses as low as 0.08 μg/kg, 1 μg/kg, and 5 μg/kg, respectively. DF‐006 in combination with the HBV nucleoside reverse transcriptase inhibitor, entecavir, further reduced HBV DNA. Antiviral efficacy in mice was associated with an increase in immune cell infiltration and decrease of hepatitis B core antigen, encapsidated pregenomic RNA, and covalently closed circular DNA in liver. At subnanomolar concentrations, DF‐006 also showed anti‐HBV efficacy in PHH with significant reductions of HBV DNA. Following dosing with DF‐006, there was upregulation of NF‐κB‐targeted genes that are involved in innate immunity. Conclusion: DF‐006 was efficacious in mouse and PHH models of HBV without any indications of overt toxicity. In mice, DF‐006 localized primarily to the liver where it potently activated innate immunity. The transcriptional response in mouse liver provides insights into mechanisms that mediate anti‐HBV efficacy by DF‐006. Abstract :